Numerical Tsunami Hazard Modelling in the Pancer Coast - Puger, East Java, Indonesia - Rozikan Rozikan; Agus Suprianto; Muhammad Aryono Adhi; Bowo Eko Cahyono (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2026)
The southern Java subduction zone is one of the major tsunami hazard sources in Indonesia due to its potential to generate large megathrust earthquakes. This study evaluates tsunami hazards from a Mw 8.7 megathrust earthquake worst-case scenario using numerical modeling with COMCOT v1.7. A five-layer nested grid system is applied to simulate tsunami generation, propagation, and inundation from the Indian Ocean to the Pancer - Puger coast, Jember Regency, Indonesia. Earthquake source parameters are defined using the Wells and Coppersmith empirical relationships, while initial seafloor deformation is calculated using the Okada elastic dislocation model. Tsunami wave dynamics are analyzed using Virtual Tsunami Gauges (VTGs). The results indicate that Puger Kulon and Mojosari villages experience the most severe impacts, with large wave amplitudes, strong currents, and inundation exceeding 20 m depths. Tsunami arrival time is about 21 to 27 minutes, providing a very limited evacuation window. The ETH (Estimated Tsunami Height) and ETA (Estimated Time of Arrival) maps show that low-lying, open coastal plains act as primary pathways for tsunami penetration. These findings emphasize the high vulnerability of the Pancer coast - Puger and the need for risk-based mitigation, improved evacuation planning, and strengthened local early warning systems.